1985
DOI: 10.1002/ajh.2830200413
|View full text |Cite
|
Sign up to set email alerts
|

Impaired IgM antibody responses to an influenza virus vaccine in adults with sickle cell anemia

Abstract: Type-specific IgM and IgG antibody responses to a polyvalent influenza vaccine were evaluated in 16 adults with sickle cell anemia, with the use of an enzyme-linked immunosorbent assay. When compared to healthy controls, 8 out of the 16 patients had decreased or undetectable postvaccination anti-influenza IgM antibody levels. These patients were found to have significantly lower serum IgM levels and nondetectable splenic tissue (by 99Tc scans), as compared to those with normal IgM responses. Impaired IgM antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 10 publications
0
28
1
2
Order By: Relevance
“…Splenectomy can provoke modifications in the immunologic state, such as increase in the total number of lymphocytes, including B-and T-cells [8,9], and can induce alterations of the humoral immunity [27-291. Morever, in the absence of functional splenic tissue, as in sickle cell anemia, impairment of antigen-specific IgM and IgG antibody responses has been reported [30]. However, in our study, half of the patients were splenectomized, and the same altered B-cell differentiation was observed in splenectomized and nonsplenectomized cases, discarding an important effect of splenectomy .…”
Section: Discussioncontrasting
confidence: 42%
“…Splenectomy can provoke modifications in the immunologic state, such as increase in the total number of lymphocytes, including B-and T-cells [8,9], and can induce alterations of the humoral immunity [27-291. Morever, in the absence of functional splenic tissue, as in sickle cell anemia, impairment of antigen-specific IgM and IgG antibody responses has been reported [30]. However, in our study, half of the patients were splenectomized, and the same altered B-cell differentiation was observed in splenectomized and nonsplenectomized cases, discarding an important effect of splenectomy .…”
Section: Discussioncontrasting
confidence: 42%
“…Five studies found that influenza vaccine was immunogenic among children and adults with seroconversion rates of 60–87% and seroprotection rates of 70–100% [5559]; however, the immune response may be blunted in children who receive chronic transfusions (90% immune response among subjects not on chronic transfusions compared with 61% among those subjects receiving chronic transfusions) [59]. One study in adults with sickle cell disease found impaired immune responses to trivalent inactivated vaccine, suggesting that the long-term effects of sickle cell disease, such as splenic atrophy, may affect immune response to vaccination [60]. Influenza vaccines are generally considered safe among individuals with sickle cell disease; however, one study suggested a 7- to 9-fold increased risk of hospitalization for sickle cell anemia after administration of trivalent inactivated vaccine [61].…”
Section: Resultsmentioning
confidence: 99%
“…High rates of alloimmunization, connective tissue diseases and transplant rejections , as well as incidences of aberrant vaccine reactivity , have bought to surface adaptive immune abnormalities in SCA. Currently, however, little has been done to characterize T and B lymphocyte phenotype, function and contribution to chronic inflammatory diseases in SCA.…”
Section: Adaptive Immune Dysfunction In Scamentioning
confidence: 99%
“…These abnormalities, including reduction in the proportion of circulating CD4+ and CD8+ T cells, dysfunction of regulatory T cells and impaired B cell IgM secretion , occur concurrent with increased immune activation and may affect vaccine reactivity in individuals with SCA. Thus, immune abnormalities in SCA may potentially explain incidences of impaired magnitude or duration of response to vaccines reported in individuals with SCA . Of note, critical studies reporting adaptive immune changes in SCA were done among SCA populations in the United States and Europe .…”
Section: Introductionmentioning
confidence: 99%